COST-BENEFIT ANALYSIS PENGELOLAAN SUMBERDAYA PESISIR TELUK BANTEN BERKELANJUTAN - Sjaifuddin . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACTBanten bay coastal zone is a unique ecosystem which has a variety potencies and problems of using some natural resources, especially in the trade off between economic growth and ecological preservation. Based on these conditions, this research aimed to identify the management feasibility of Banten Bay coastal resources. An extended cost-benefit analisys which integrated the external and/or environmental benefits, damage cost and cost of society of environmental protection measures was used as methods of this research. The result of this research showed that all of management options of Banten Bay coastal resources were feasible to be developed. Based on comparative performance index, it was known that sustainable mangrove management, sustainable harvest and beach protected areas were the most feasible management option to be implemented in the management of Banten Bay coastal resources. Key words: cost-benefit analysis, sustainable management, coastal and marine resources.